Forward-backward asymmetry of Drell-Yan lepton pairs in pp collisions at root s=8 TeV - (:unkn) unknown (SPRINGER, 2016)
A measurement of the forward-backward asymmetry A(FB) of oppositely charged lepton pairs (mu mu and ee) produced via Z/gamma* boson exchange in pp collisions at root s = 8 TeV is presented. The data sample corresponds to an integrated luminosity of 19.7 fb(-1) collected with the CMS detector at the LHC. The measurement of AFB is performed for dilepton masses between 40 GeV and 2 TeV and for dilepton rapidity up to 5. The AFB measurements as a function of dilepton mass and rapidity are compared with the standard model predictions.